Natural products in traditional Chinese medicine for renal fibrosis: a comprehensive review - Zhao, Qianqian; Jin, Meihua; Zhao, Qiang; Wang, Zhimei; Zhao, Chun; Xue, Xiaocong; Qiao, Xikai; Qu, Peng; Han, Donghe; Tao, Ran (Frontiers in Pharmacology, 2025)
Renal fibrosis represents the terminal pathological manifestation of most chronic kidney diseases, driving progressive loss of renal function. Natural products have emerged as promising therapeutic agents for preventing and ameliorating renal fibrosis due to their multi-target efficacy and favorable safety profiles. In this review, we conducted a comprehensive literature search on PubMed using the keywords “natural product” and “renal fibrosis” from 2004 to 2025, identifying 704 relevant articles. We systematically categorize and discuss the biological effects of key natural products and formulations with antifibrotic potential, focusing on five major classes: glycosides, flavonoids, phenolic compounds, anthraquinones, and terpenoids. Representative compounds from each category are highlighted for their mechanisms of action, including modulation of oxidative stress, inflammation, autophagy, and fibrosis signaling pathways. This review aims to provide a theoretical foundation for the development of natural product-based therapies to combat renal fibrosis, offering insights into their therapeutic potential and future research directions.